Vascular Endothelial Growth Factor Is Regulated by the Canonical and Noncanonical Transforming Growth Factor-β Pathway in Synovial Fibroblasts Derived from Osteoarthritis Patients. (29th September 2019) - Takano, Shotaro; Uchida, Kentaro; Shoji, Shintaro; Itakura, Makoto; Iwase, Dai; Aikawa, Jun; Mukai, Manabu; Sekiguchi, Hiroyuki; Inoue, Gen; Takaso, Masashi
Abstract : Background . Previous studies suggest the presence of an association of vascular endothelial growth factor (VEGF) with osteoarthritis (OA) severity and pain in patients with knee OA. VEGF expression in human synovial fibroblasts (SFs) is induced by transforming growth factor-beta (TGF β ). However, the signaling pathway governing TGF β -mediated regulation of VEGF in SFs has not been identified. Methods . OA patients who underwent total knee arthroplasty had their synovial tissue (SYT) extracted and the constituent SFs cultured. The cells were stimulated with culture medium (control), human recombinant TGF β (hrTGF β ), hrTGF β + ALK5 inhibitor SB505124, hrTGF β + transforming growth factor activating kinase 1 (TAK1) inhibitor (5Z)-7-oxozeaenol, or hrTGF β + p38 inhibitor SB203580 for 6 h. VEGF mRNA expression in SFs was examined using real-time polymerase chain reaction and VEGF protein production in the cell supernatant was examined using enzyme-linked immunosorbent assay. Additionally, phosphorylated levels of SMAD2 and p38 were examined using western blotting. Results . ALK5 (SB505124) and TAK1 (5Z-oxozeaenol) inhibitors completely suppressed TGF β -induced VEGF mRNA expression and VEGF protein production. Both SB505124 and 5Z-oxozeaenol also suppressed SMAD2 and p38 phosphorylation. The p38 inhibitor (SB203580) partially inhibited TGF β -mediated VEGF mRNA and VEGF protein production. Conclusion . TGF β -mediated regulation of VEGF expression and VEGF protein production in the SYT of OA patients occurs through both the canonical and noncanonical pathway.